Amidinium‐Containing 2D [MnCr] Dimetallic Oxalate‐Based Networks – The Influence on Structure and Magnetism Explored by Combining Experience and Theory. Issue 26 (16th August 2016) - Maxim, Catalin; Saureu, Sergi; de Graaf, Coen; Ferlay, Sylvie; Hosseini, Mir Wais; Robert, Vincent; Train, Cyrille
Abstract : Three X 2+ bisamidinium dications are inserted into oxalate‐based dimetallic [MnCr] compounds of formula X[Mn II (CH3 OH)Cr III (ox)3 ]2 · n S [X 2+ = C14 N4 H20 2+ (cationA 2+, compound1 ), C14 O2 N4 H20 2+ (cationB 2+, compound2 ), C16 N4 H24 2+ (cationC 2+, compound3 ); n = 4 (1 –2 ), 2 (3 ); S = CH3 OH (1 –2 ), CH3 CN (3 ); ox = oxalate]. Single‐crystal X‐ray analysis of1 –3 reveals that Mn–Cr oxalate‐bridged dimetallic coordination networks form corrugated two‐dimensional (2D) layers based on heptacoordinate Mn II ions surrounded by six oxygen atoms from three bis‐bidentate oxalate ions and one oxygen atom from a coordinated methanol molecule. In1 –3, the observed coordination environments of the Mn II ions are close to capped trigonal prismatic (CTPR‐7) according to continuous shape measurements (CSM). Curie–Weiss temperatures of 0.62, 0.42, and 0.54 K for1 –3, respectively, were deduced from the magnetic susceptibility measurements and reveal dominant ferromagnetic exchange interactions. Ab initio calculations up to the DDCI‐2 level were performed on [MnCr] dimeric units and allowed the evaluation of the exchange interactions in1 –3 . Abstract : Three oxalate‐based dimetallic [MnCr] compounds with intercalated bisamidinium dications are studied, and magnetostructural correlations are provided.